Isolation and Identification of a Siderophore Producing and Antagonistic Cold Tolerant (psychrotrophic) Pseudomonas sp. LHSP1: IDENTIFICATION OF COLD TOLERANT PSEUDOMONAS SP - Kasana, Ramesh Chand; Singh, Sunil Kumar (Annals of Arid Zone, 2024)
Present study was conducted for isolation and selection of cold tolerant bacteria with plant growth promoting attributes. Among sixty-one psychrotrophic bacteria isolated from cold environments soils of the Western Himalayas, India, seven were found positive for siderophore production at low temperature of 5°C. Of these seven isolates, LHSP1 was selected for further studies on the basis of its ability to produce highest amount of siderophore, showing largest orange halo around the growth in plate assay. Strain showed maximum production of siderophore, 82.5 and 87.1% siderophore unit (psu) after three days of incubation at temperature of 20°C and 28°C, respectively. It showed strong antagonistic activity against two fungal pathogens, Fusarium equiseti CZCU-2 and F. solani CZGN-9 showing up to 65.0 and 55.6% inhibition at 20°C and 28°C, respectively. In the medium, supplemented with 0.30% of tryptophan, it produced 47.25 μg mL−1 of indole acetic acid (IAA) after three days of incubation. This strain showed very good growth in the presence of 20% polyethylene glycol (PEG) 6000 and was able to grow and survive at 30% PEG 6000. The 16S rRNA gene-sequencing was carried out and the sequence was submitted to NCBI with accession number MW627227. Based on 16S rRNA gene-sequencing studies, isolate was identified as Pseudomonas sp. LHSP1